Occurrence of Giardia cysts and Cryptosporidium oocysts in activated sludge samples in Campinas, SP, Brazil Ocorrência de cistos de Giardia e oocistos de Cryptosporidium em amostras de lodo ativado em Campinas, SP, Brasil - Luciana Urbano Santos; Taís Rondello Bonatti; Romeu Cantusio Neto; Regina Maura Bueno Franco (Revista do Instituto de Medicina Tropical de São Paulo, 2004)
Giardia and Cryptosporidium have caused several outbreaks of gastroenteritis in humans associated with drinking water. Contaminated sewage effluents are recognized as a potential source of waterborne protozoa. Due to the lack of studies about the occurrence of these parasites in sewage samples in Brazil, we compared the efficiency of two procedures for concentrating cysts and oocysts in activated sludge samples of one sewage treatment plant. For this, the samples were submitted to i) concentration by the ether clarification procedure (ECP) and to ii) purification by sucrose flotation method (SFM) and aliquots of the pellets were examined by immunofluorescence. Giardia cysts were present in all samples (100.0%; n = 8) when using ECP and kit 1 reagents, while kit 2 resulted in six positive samples (85.7%; n = 7). As for SFM, cysts were detected in 75.0% and 100.0% of these samples (for kit 1 and 2, respectively). Regarding Cryptosporidium, two samples (25.0%; kit 1 and 28.5% for kit 2) were detected positive by using ECP, while for SFM, only one sample (examined by kit 1) was positive (12.5%). The results of the control trial revealed Giardia and Cryptosporidium recovery efficiency rates for ECP of 54.5% and 9.6%, while SFM was 10.5% and 3.2%, respectively. Considering the high concentration detected, a previous evaluation of the activated sludge before its application in agriculture is recommended and with some improvement, ECP would be an appropriate simple technique for protozoa detection in sewage samples. Giardia e Cryptosporidium causaram vários surtos epidêmicos de gastroenterite, associados à água potável. Efluentes de esgoto contaminados foram incriminados como uma fonte potencial de cistos e oocistos. Uma investigação foi conduzida para verificar a presença de cistos de Giardia e oocistos de Cryptosporidium em amostras de lodo ativado de uma Estação de Tratamento de Esgoto. Para isto as amostras foram submetidas: i) a concentração pelo processo de clarificação com éter (ECP) e ii) método de purificação por flutuação em sacarose (SFM) e, as alíquotas dos sedimentos foram examinadas por imunofluorescência. Cistos de Giardia estiveram presentes em todas as amostras avaliadas (100,0%; n = 8) quando utilizado ECP e kit 1, enquanto o kit 2 resultou em 6 amostras positivas (85,7%; n = 7). Para SFM, cistos de Giardia foram detectados em 75,0% e 100,0% destas amostras (para kit 1 e 2 respectivamente). Considerando os oocistos de Cryptosporidium, duas amostras (25,0%; kit 1 e 28,5% kit 2) foram positivas usando-se ECP enquanto para SFM, apenas uma amostra (examinada pelo kit 1) foi positiva (12,5%). Os resultados do experimento-controle revelaram que as taxas de recuperação para Giardia e Cryptosporidium, quando utilizado ECP foi de 54,5% e 9,6% e para SFM, foi de 10,5% e 3,2%, respectivamente. Considerando a detecção de alta concentração desses protozoários, é recomendada a avaliação prévia do lodo ativado antes de sua aplicação na agricultura e, com alguma melhora, ECP pode ser uma técnica apropriada e simples para a detecção de protozoários em amostras de esgoto.